Evolution and Functional Insights of Different Ancestral Orthologous Clades of Chitin Synthase Genes in the Fungal Tree of Life - Li, Mu; Jiang, Cong; Wang, Qinhu; Zhao, Zhongtao; Jin, Qiaojun; Xu, Jin-Rong; Liu, Huiquan (Frontiers in Plant Science, 2016)
Chitin synthases (CHSs) are key enzymes in the biosynthesis of chitin, an important structural component of fungal cell walls that can trigger innate immune responses in host plants and animals. Members of CHS gene family perform various functions in fungal cellular processes. Previous studies focused primarily on classifying diverse CHSs into different classes, regardless of their functional diversification, or on characterizing their functions in individual fungal species. A complete and systematic comparative analysis of CHS genes based on their orthologous relationships will be valuable for elucidating the evolution and functions of different CHS genes in fungi. Here, we identified and compared members of the CHS gene family across the fungal tree of life, including 18 divergent fungal lineages. Phylogenetic analysis revealed that the fungal CHS gene family is comprised of at least 10 ancestral orthologous clades, which have undergone multiple independent duplications and losses in different fungal lineages during evolution. Interestingly, one of these CHS clades (class III) was expanded in plant or animal pathogenic fungi belonging to different fungal lineages. Two clades (classes VIb and VIc) identified for the first time in this study occurred mainly in plant pathogenic fungi from Sordariomycetes and Dothideomycetes. Moreover, members of classes III and VIb were specifically up-regulated during plant infection, suggesting important roles in pathogenesis. In addition, CHS-associated networks conserved among plant pathogenic fungi are involved in various biological processes, including sexual reproduction and plant infection. We also identified specificity-determining sites, many of which are located at or adjacent to important structural and functional sites that are potentially responsible for functional divergence of different CHS classes. Overall, our results provide new insights into the evolution and function of members of CHS gene family in the fungal kingdom. Specificity-determining sites identified here may be attractive targets for further structural and experimental studies.